Sabah (Malaysia) â Australia Relations: An Historical Observation - Idris, Rizal Zamani; Bala, Bilcher; Morshidi, Azizan H (TAWARIKH, 2013)
ABSTRACT: The purpose of this paper is to examine the historical development of the relations between the state of Sabah (Malaysia) and Australia. These two political entities share a lot in common due to their historical past. They have both known one another since the 18th century. Notably, both countries had a British colonial background that has been founded by private explorers from England. Nonetheless, they experienced different fates from the start of the 20th century. Unlike Sabah, Australia became the permanent residence to thousands of Anglo-Saxon immigrants. The colonization process of this ethnic group eventually became the dividing line between Australia and Sabah as well as other countries within the East Asian region. However, the long-standing relationship between Sabah and Australia manifests that the foundation of the relationship is strong hence shall be further strengthened. This is an early attempt to trace the historical connections between Sabah (Malaysia) and Australia. Hence, further research is necessary in order to appreciate and further strengthen their relationship for mutual benefits.KEY WORDS: Sabah, Australia, historical development, relations of two nations, Â and relationship for mutual benefits.Â Â Â Â About the Authors: Rizal Zamani Idris, Assoc. Prof. Dr. Bilcher Bala, and Azizan H. Morshidi are Lecturers at the School of Social Sciences UMS (Malaysia University of Sabah), Jalan Beg Berkunci, Kota Kinabalu, Sabah, Malaysia. Corresponding author is rizal.idris@gmail.comHow to cite this article? Idris, Rizal Zamani, Bilcher Bala & Azizan H. Morshidi. (2013). âSabah (Malaysia) â Australia Relations: An Historical Observationâ in TAWARIKH: International Journal for Historical Studies, Vol.4(2) April, pp.151-170. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 11, 2013); Revised (March 12, 2013); and Published (April 28, 2013).